The economic development of the third World since 1900 - Bairoch, Paul (Methuen, 1975)
It has been Professor Bairoch’s aim in this book to examine the development of under-developed countries (including China) during the present century and through the use of comparative statistics to formulate a diagnosis of their growth. His analysis includes, whenever relevant, a comparison between the present economic progress of Third World countries and that of the developed countries at the time of their ‘take off’. Special attention has also been given to China’s unique path of development.